Evaluation of the effectiveness of using platelet rich fibrin (PRF) as a sole grafting material and membrane in augmentation of dehiscence and fenestration defects encountered during dental implant surgery - Abbas, Ahmed M.; Bede, Salwan Y.; Alnumay, Shefaa H. (Journal of Baghdad College of Dentistry, 2019)
Background: Bone regeneration in dehiscence and fenestration defect can be improved with the use of platelet rich fibrin (PRF) that provides a scaffold for new bone regeneration. This study was conducted to assess the effectiveness of PRF as a graft material and membrane in dehiscence and fenestration defects. Materials and Methods: This prospective clinical study included patients who received dental implants that demonstrated peri-implant defects which were augmented using Leukocyte- PRF (L-PRF) or Advanced-PRF (A-PRF). Twenty four weeks postoperatively the defect resolution and the density of regenerated bone were assessed by CBCT and re-entry surgery. The assessment also included measurement of primary and secondary implant stability using Periotest® M, success rate and complication rate of the installed implants. Results: The mean overall intraoperative defect size was 29.44 (± 14.1) mm2, postoperatively it became 2.07 (± 3.6) mm2 with a statistically significant difference (p= < 0.0001). There was no significant difference between L-PRF and A-PRF. Defect resolution ranged from 80% to 100% with a mean of 95.7% (± 6.7%). Defects that showed complete resolution were significantly smaller in size (21.2± 7 mm2) than those that showed partial resolution (44.4± 11 mm2). The overall mean primary stability recorded was 2.9 (± 1.6) Periotest values (PTV) and overall mean secondary stability was -0.22 (±1.4) (P<0.0001).The overall mean HU of the newly formed peri-implant bone was 385.7 (± 77.4). Conclusions: PRF as the sole graft material for peri-implant defects results in complete defect resolution in small to moderate defects, larger defects may require the addition of bone substitute to achieve complete defect resolution.